2018
DOI: 10.1038/s41593-018-0172-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel pyramidal cell type promotes sharp-wave synchronization in the hippocampus

Abstract: To support cognitive function, the CA3 region of the hippocampus performs computations involving attractor dynamics. Understanding how cellular and ensemble activities of CA3 neurons enable computation is critical for elucidating the neural correlates of cognition. Here we show that CA3 comprises not only classically described pyramid cells with thorny excrescences, but also includes previously unidentified 'athorny' pyramid cells that lack mossy-fiber input. Moreover, the two neuron types have distinct morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
106
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(130 citation statements)
references
References 57 publications
15
106
0
Order By: Relevance
“…CA1 pyramidal neurons containing IGFBP2 may also enable parallel information processing [21] in celltype-specific firing patterns [22] since we found IGFBP2 did not interfere with CA1-interneuron spiking. We found that IGFBP2 enhanced both the evoked and spontaneous neuronal excitability and the fidelity of spike transmission of CA1 pyramidal neurons by ≈5.3 excitatory inputs.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…CA1 pyramidal neurons containing IGFBP2 may also enable parallel information processing [21] in celltype-specific firing patterns [22] since we found IGFBP2 did not interfere with CA1-interneuron spiking. We found that IGFBP2 enhanced both the evoked and spontaneous neuronal excitability and the fidelity of spike transmission of CA1 pyramidal neurons by ≈5.3 excitatory inputs.…”
Section: Discussionmentioning
confidence: 59%
“…[21,22] IGFBP2 enhanced mEPSC frequency without changing the PPR, indicating a novel role of IGFBP2 in glutamate receptor kinetics. Among the pyramidal neurons, IGFBP2 preferentially excited L cells rather than H cells.…”
Section: Discussionmentioning
confidence: 92%
“…Reveals Three Cell Classes in the Human HIPP: NS, BS1, and BS2 Given that the motion-related effect on EAP waveforms is abundant in deep-brain structures, we next focused our analyses on the HIPP, a deep-brain region where, in rodents, numerous excitatory and inhibitory neural classes have been identified (Freund and Buzsá ki, 1996;Graves et al, 2012;Hunt et al, 2018;Klausberger et al, 2003;Harris et al, 2018). We applied our analysis to the 69 units exhibiting the strongest cardiacrelated AMP MI (the subset of cells with the strongest AMP modulation during the cardiac cycle, mean AMP MI = 4.1 ± 3.1; this subset was selected by comparing the EAP of an individual cell to the bootstrap shuffled waveforms at p < 0.05, STAR Methods).…”
Section: Variability In Eap Features During Cardiac Motionmentioning
confidence: 99%
“…Moreover, macroscopic cell loss of CA1 should be sub-characterized by the differential loss of deep versus superficial neurons (Towfighi et al, 2004), which could vary widely among patients and be a source of variation in epilepsy expression. The implications of heterogeneity within microcircuits extend to other brain areas, where these characteristics are beginning to be understood rather than being an exception of CA1 (Krook-Magnuson et al, 2012;Varga et al, 2010;Hunt et al, 2018). Because this connectivity bias is preserved in chronically epileptic animal models (Armstrong et al, 2016), determining how seizures and interictal abnormalities are expressed within heterogeneous microcircuits is a valid concern.…”
Section: Heterogeneity Within Microcircuits: Possible Source Of Indivmentioning
confidence: 99%